Development Of Interactive Multimedia Based Articulate Storyline 3 on The Main Discussion Volume of Space Building at Ulil Albab Caruban Primary School - Hidayat, Melingga Nabilla; Wedi, Agus; Fadhli, Muhibuddin (Proceedings Series of Educational Studies, 2024)
The aim of this research is to develop interactive multimedia based Articulate Storyline 3 on the subject of building volume, and to assess the feasibility and effectiveness of the product. The development model used is ADDIE (Analyze, Design, Development, Implementation, Evaluation) developed by Robert Maribe Branch. The product that has been developed is tested for validity by media experts and material experts, after which it is tested on class VI students at SD Ulil Albab Caruban. The validity test results of media experts showed a value of 88.09% and material experts showed a value of 91.67%. The results of the trial on 30 students showed a score of 81.33%. Meanwhile, the effectiveness test carried out has a significant difference because Sig. (2-tailed) has a value of 0.000 less than 0.05 which shows that there is a difference between pre-test and post-test. From this description it can be concluded that the interactive multimedia developed is valid and effective for use in learning. Keywords: Interacti